A202 TOFACITINIB FOR THE TREATMENT OF ULCERATIVE COLITIS: UP TO 5.4 YEARS OF SAFETY DATA FROM GLOBAL CLINICAL TRIALS. (15th March 2019) - Sandborn, W J; Panés, J; Panaccione, R; D'Haens, G; Sands, B E; Su, C; Moscariello, M; Jones, T V; Pedersen, R D; Friedman, G S; Lawendy, N; Chan, G
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis (UC). Efficacy and safety of tofacitinib as UC induction and maintenance therapy were evaluated in Phase (P)2 1 and P3 2 randomized, placebo-controlled studies, and an ongoing, open-label extension (OLE) study. 3 Aims: To report updated tofacitinib safety analyses from the UC program, with exposure up to 5.4 years. Methods: Patients (pts) who received placebo, tofacitinib 5 or 10 mg twice daily (BID) were analyzed as 2 cohorts: Maintenance (P3 maintenance, N=592) and Overall (pts receiving tofacitinib 5 or 10 mg BID in P2, P3, or the OLE study, N=1157; 2051 pt-years' exposure; data at Nov 2017). Proportions and incidence rates (IRs; pts with events per 100 pt-years) were evaluated for adverse events (AEs) of special interest. Opportunistic infections, malignancies, major adverse cardiovascular events (MACE), and gastrointestinal perforations were reviewed by independent adjudication committees. Results in the Overall Cohort based on the previous Dec 2016 data cut are presented for context. Results: 1157 pts received ≥1 dose of tofacitinib 5 or 10 mg BID. Demographics and disease characteristics were generally similar among treatment groups across cohorts. For the Overall Cohort, most pts (N=956, 83%) received an average tofacitinib dose of 10 mg BID. IRs for AEs of special interest were: death, 0.2; serious infection, 1.9; opportunistic infection, 1.2; herpes zoster, 3.8; malignancy (excluding non-melanoma skin cancer [NMSC]), 0.6; NMSC, 0.8; MACE, 0.3; and gastrointestinal perforations, 0.1. Conclusions: The safety profile of tofacitinib in pts with UC was manageable and similar to the tofacitinib rheumatoid arthritis program, and that of other UC therapies including biologics. IRs for AEs of special interest did not increase with longer exposure relative to previously reported analyses from the OCTAVE program. A dose-dependent risk of herpes zoster was observed. 1. Sandborn WJ et al. N Engl J Med 2012;367:616–24. 2. Sandborn WJ et al. N Engl J Med 2017;376:1723–36. 3. Lichtenstein GR et al. Am J Gastroenterol 2017;112(S1):Abstract 714. Funding Agencies: NonePfizer Inc